Internal Control System, Sustainable Management and Service Delivery of NGO’s in Nigeria: An Empirical Analysis - Rafindadi, Abdulkadir Abdulrashid; Olanrewaju, Zakariyah Aliyu (International Review of Management and Marketing, 2019)
This study examines how internal control system affects goal attainment and sustainable management in NGOs. Data was collected from primary source through the administration of three hundred and fifty-two (352) copies of questionnaire to the respondents selected through multi-stage sampling techniques from forty-four sample NGOs in North-West Nigeria. Data retrieved from survey were analysed using descriptive and inferential statistics through mean, standard deviation, correlation matrix and multiple regression using SPSS version 23. Major findings from this study revealed that a 1 % change in the standardized regression coefficient will result to about 1 % increase in sustainability of services in NGOs. Impliedly, a unit increase in any of the predictor variables used in the study will results in the corresponding increase in sustainability of services in NGOs. Following to this development, it is possible to argue and conclude that, any observed variations in the sustainability of NGOs in terms of efficient management and good service delivery are seemingly caused by the good or bad of that NGOs established internal control system. The study also discovered how the failure of government to participate actively in generating counterpart funding and poor attitude towards strengthening of the sustainability of services results to poor service delivery to the targeted beneficiaries. As a result of these findings, it is recommended that government should support interventions actively through the provision of counterpart funding and by enforcing those policies that will be impactful in strengthening the activities of NGOs. Keywords: Internal control system, NGOs, Goal attainment, sustainable management. Cross sectional models, survey methods. JEL Classifications: C31, C42, L31, L78, L78 DOI: https://doi.org/10.32479/irmm.7773